PENGARUH PENAMBAHAN LIMBAH BATU BATA MERAH BUKITTINGGI SEBAGAI FILLER PADA CAMPURAN AC-WC DENGAN PENGUJIAN MARSHALL - Misbah, Misbah; Pratiwi JF, Anggun; Arman, Arman; Mulyati, Mulyati; Rofifah, Jihan (ITP Press, 2023)
The existence of highways is needed in the development of an area. The problems that are often encountered in the construction of highways are excessive vehicle loads than permitted, less than optimal road maintenance and the influence of asphalt mixture factors, so that roads are often found to be damaged before the design life is reached. To improve the quality of road pavement construction, it is necessary to conduct research on mixed innovations used or adding other additives to the pavement construction mixture, so that better mixed quality is produced. One of the types of research that can be done is to use the method of making test objects by conducting experiments in the laboratory by analyzing the effect of adding Bukittinggi red brick waste as a filler to the AC-WC mixture with the Marshall test. From the results of the research with the Marshall test that has been carried out, with the title